EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE (ETH) PADA SISWA KELAS X SMA NEGERI 8 TAKALAR - Wahyuddin, Wahyuddin; Nurcahaya, Nurcahaya (Al-Khawarizmi, 2018)
This type of research was pre-experimental research (one group pretest-posttes design) which involved a class as an experimental class that aimed to determine the effectiveness of the Everyone Is A Teacher Here (ETH) Active Learning Model in Mathematics learning at 10th grade students in SMA Negeri 8 Takalar. This study referred to the criteria of the effectiveness of learning, namely: (1) individual learning completeness, gain and classical, (2) students’ activity in learning process, and (3) students’ response in learning process, (4) improvement of students' mathematics learning outcomes after the application of active learning model type Everyone Is A Teacher Here.Subjects in this study were students of class X MIA 3 SMA Negeri 8 Takalar as many as 30 students. The research was conducted for 6 meetings. Data collection techniques used are the test of learning outcomes, student activity observation sheets and the implementation of learning, and questionnaire responses of students. Data analysis techniques used were descriptive analysis to describe the learning outcomes, student activities, learning implementation, and student responses and infrensial analysis with normality test and hypothesis testing with One Sample t-test. The results shown that: (1) the average score of students' mathematics learning outcomes before being applied Active learning model Type Everyone Is A Teacher Here (ETH) was 85.7 and in the high category, where 27 students or 90% reach individual completeness, 3 students or 10% did not reach the completeness of individuals and this mean that the completeness of the classical was achieved with a normalized gain value of 0.78 in the high category. (2) Student activity in following learning with average percentage of student active activity is 83,3%. (3) The average of learning activity is 3.57 and it was in the category was done very well. (4) Student response to learning mathematics with Active Learning Model Type Everyone Is A Teacher Here (ETH) students who responded positively with the percentage of 85.1% and 14.9% of students who responded negatively. Thus it can be concluded that the Active Model of Learning Type Everyone Is A Teacher Here (ETH) was effectively applied in learning mathematics of students of class X SMA Negeri 8 Takalar.